2020
DOI: 10.1002/asna.202013682
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to generate a catalogue of potential historical novae

Abstract: Ancient Chinese, Korean, and Vietnamese observers left us records of celestial sightings, the so‐called “guest stars” dated up to ∼2500 years ago. Their identification with modern observable targets could open interesting insights into the long‐term behavior of astronomical objects, as shown by the successful identification of eight galactic supernovae. Here, we evaluate the possibility to identify ancient classical novae with presently known cataclysmic variables (CVs). For this purpose, we have developed a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The analysis of historical astronomical records has become an important resource for research on long-term variability of stars (Fujiwara et al 2004;Fujiwara and Yamaoka 2005;Hamacher and Frew 2010;Hamacher 2018), comet orbits (Neuhäuser et al 2018), meteoritic events (Hamacher 2009), novae (Shara et al 2007;Duerbeck 2008;Patterson et al 2013;Miszalski et al 2016;Shara et al 2017), supernovae (Stephenson 1976;Clark and Stephenson 1977;Yau 1988;Stephenson and Green 2002;Green and Stephenson 2003;2017;Zhou et al 2018;Green 2019) and close interacting binary stars. Stellarium can be used to demonstrate transient phenomena like comets or "guest stars" recorded by historians and chroniclers (Zotti and Wolf 2020a;Hoffmann 2019b;Hoffmann et al 2020;Hoffmann and Vogt 2020a).…”
Section: Skycultures and Astrophysicsmentioning
confidence: 99%
“…The analysis of historical astronomical records has become an important resource for research on long-term variability of stars (Fujiwara et al 2004;Fujiwara and Yamaoka 2005;Hamacher and Frew 2010;Hamacher 2018), comet orbits (Neuhäuser et al 2018), meteoritic events (Hamacher 2009), novae (Shara et al 2007;Duerbeck 2008;Patterson et al 2013;Miszalski et al 2016;Shara et al 2017), supernovae (Stephenson 1976;Clark and Stephenson 1977;Yau 1988;Stephenson and Green 2002;Green and Stephenson 2003;2017;Zhou et al 2018;Green 2019) and close interacting binary stars. Stellarium can be used to demonstrate transient phenomena like comets or "guest stars" recorded by historians and chroniclers (Zotti and Wolf 2020a;Hoffmann 2019b;Hoffmann et al 2020;Hoffmann and Vogt 2020a).…”
Section: Skycultures and Astrophysicsmentioning
confidence: 99%
“…For comparison, Kepler's and Tycho's supernovae are thought to have reached m peak −3 and at m peak −4, respectively (Green & Stephenson 2003). We thus checked for positional coincidences in several compilations of historical guest star observations (Tse-Tsung 1957;Stephenson 1976Stephenson , 1971Clark & Stephenson 1976;Yang et al 2005;Stephenson & Green 2009;Hoffmann et al 2020). There were no matches closer than about 18 • , but we did uncover one potential counterpart: # 45 in Stephenson & Green (2009).…”
Section: V341 Ara As An Old Novamentioning
confidence: 99%
“…In this paper, we critically discuss recent publications Hoffmann et al 2020;Hoffmann & Vogt 2020a, 2020band Vogt et al 2019) on historical East Asian guest stars, where they mainly aimed at identifying nova candidates. However, as we will show, there are many strong shortcomings in their work.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%
“…This is presented here. In Section 2, we discuss the first two papers on previous historical SNe and novae (Hoffmann 2019; Vogt et al 2019), in Section 3 additional papers on their nova suggestions (Hoffmann et al 2020;Hoffmann & Vogt 2020a, 2020b, and in Section 4 we finish with a summary and final remarks. 1 Neuhäuser et al (2021a) have shown in detail that the sources used for two of the highlights in Hoffmann and Vogt (2020b), namely a presumable new historical SN AD 1 The papers by Vogt et al (2019), ), Hoffmann et al (2020, and Vogt (2020a, 2020b) were submitted without the consent of RN and after the participation of SH in the project had been terminated in a mutual agreement between RN and SH in February 2019.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%